Le mouvement ouvrier dans l’art académique espagnol : une légitimité politique contrariée - Stéphanie Demange (Cahiers de Civilisation Espagnole Contemporaine)
In the Spain of the Bourbon Restoration, the rise of social discontent made it increasingly difficult to sustain the myth of political cohesion. The paintings exhibited in the regime's National Fine Arts Exhibitions showed these major social transformations, reflecting in a very contemporary repertoire the emergence of a «social question» in which strikers and anarchists were the leading figures. Academic art thus played a full part in the creation and dissemination of representations of the workers' movement, at a time when the latter was emerging and beginning to mobilise. This article aims to characterise the contribution of the cultural institution to the imagery of the Spanish workers' movement in the late 19th-century, between new visibility and phenomena of delegitimization.